PENGARUH PERHATIAN ORANG TUA, LINGKUNGAN BELAJAR, PEMANFAATAN SARANA TERHADAP HASIL BELAJAR - Pemi Zurriyatina; I Komang Winatha; Nurdin Nurdin (FKIP Unila, 2014)
This study aims to determine the effect of parents affection, environment’s study and the utilization of facility in school on learning outcomes IPS Terpadu. The population are 40 students. The method in this research is descriptive verification with ex post facto and surveys approach. The first second and third hypothesis testing using simple linear regression. The fourth hypothesis using multiple linear regression. Based on the analysis of the data obtained the results: (1)there is the effect of the parents affection on learning outcomes IPS Terpadu, (2)there is the effect of the environment’s study in school on learning outcomes IPS Terpadu, (3)there is the effect of the the utilization of facility in school on learning outcomes on learning outcomes IPS Terpadu, (4)there is the effect of the parents affection, environment’s study and the utilization of facility in school on learning outcomes IPS Terpadu.Penelitian ini bertujuan untuk mengetahui pengaruh perhatian orang tua lingkungan belajar dan pemanfaatan sarana belajar di sekolah terhadap hasil belajar IPS Terpadu. Populasi penelitian berjumlah 40 siswa. Metode penelitian deskriptif verifikatif dengan pendekatan ex post facto dan survey. Pengujian hipotesis pertama, kedua, dan ketiga menggunakan regresi linier sederhana. Pengujian hipotesis keempat menggunakan regresi linier multiple. Berdasarkan analisis data diperoleh hasil penelitian sebagai berikut: (1)ada pengaruh perhatian orang tua terhadap hasil belajar IPS Terpadu, (2)ada pengaruh lingkungan belajar terhadap hasil belajar IPS Terpadu, (3)ada pengaruh pemanfaatan sarana belajar di sekolah terhadap hasil belajar IPS Terpadu, (4)ada pengaruh perhatian orang tua, lingkungan belajar di sekolah, dan pemanfaatan sarana belajar di sekolah terhadap hasil belajar IPS Terpadu.Kata kunci: lingkungan, perhatian orang tua, sarana